The Role of Muhammadiyah in the Development of Digital Literacy in Islamic Religious Education: A Library Research Study - Kharisma Azam Rangkuti; Wahyu Riswanda; Rizka Harfiani; Mawaddah Nasution (Global Education Journal, 2026)
This study aims to analyze Muhammadiyah's role in developing digital literacy in Islamic Religious Education in the digital era. The development of information technology has brought significant changes to the learning process, requiring Islamic education to adapt to technological developments without abandoning Islamic values. This study employed a qualitative approach with library research. Data were obtained through various scientific journal articles, books, and documents related to Muhammadiyah, digital literacy, and Islamic Religious Education. Data collection was conducted through documentation studies, while data analysis utilized content analysis with the stages of data reduction, data presentation, and conclusion drawing. The results indicate that Muhammadiyah plays a significant role in developing digital literacy through the integration of digital media into Islamic Religious Education learning, strengthening digital da'wah (preaching), developing Islamic digital ethics, improving teacher competency, and strengthening technology-based organizational governance. The use of digital technology helps improve learning effectiveness, critical thinking skills, and students' religious character. Furthermore, Muhammadiyah actively utilizes social media and digital platforms as a means of disseminating moderate Islamic values and religious education that is adaptive to current developments. Despite persistent obstacles such as limited infrastructure and limited digital literacy skills among some human resources, the development of digital literacy continues to have a positive impact on the transformation of Islamic Religious Education in the digital era. This research implies that strengthening digital literacy based on Islamic values needs to be continuously developed to create Islamic education that is innovative, moderate, and relevant to the needs of modern society.